Tribological testing of self-mated nanocrystalline diamond coatings on Si3N 4 ceramics - Abreu, C. S. (2006)
Due to their much lower surface roughness compared to that of microcrystalline diamond, nanocrystalline diamond (NCD) films are promising candidates for tribological applications in particular when deposited on hard ceramic materials such as silicon nitride (Si3N4). In the present work, microwave plasma assisted chemical vapour deposition of NCD is achieved using Ar/H2/CH4 gas mixtures on plates and ball-shaped Si3N4 specimens either by a conventional continuous mode or a recently developed pulsed regime. The microstructure, morphology, topography and purity of the deposited films show typical NCD features for the two kinds of substrate shapes. Besides, tribological characterisation of the NCD/Si3N4 samples is carried out using self-mated pairs without lubrication in order to assess their friction and wear response. Worn surfaces were studied by SEM and AFM topography measurements in order to identify the prevalent wear mechanisms. Friction values reached a steady-state minimum of approximately 0.03 following a short running-in period where the main feature is a sharp peak which attained a maximum around 0.45. Up to the critical load of 35 N, corresponding to film delamination, the equilibrium friction values are similar, irrespective of the applied load. The calculated wear coefficient values denoted a very mild regime (K ~ 1x10-8 mm3N-1m-1) for the self-mated NCD coatings. The predominant wear mechanism was identified as self-polishing by micro-abrasion.